Evaluating the effectiveness of a comprehensive patient education intervention in a hybrid model of cardiac rehabilitation: A pilot study - Gustavo Arrieta-Bartolomé; Marta Supervia; Alessandra Bertha Castillo Velasquez; Antonia Delgado-Montero; Irene Méndez; Mª. Ángeles Ortega Orduñez; Olga Arroyo-Riaño; Crystal Aultman; Paul Oh; Gabriela Lima de Melo Ghisi (Elsevier, 2022)
Objective: To evaluate the effectiveness of a comprehensive educational intervention in a hybrid model of cardiac rehabilitation in Spain during the COVID-19 pandemic. Methods: In a prospective pretest-posttest pilot study a pooled sample of patients attending hybrid cardiac rehabilitation in Spain received a culturally-adapted education intervention for 6 weeks. Participants completed surveys at pre- and post-rehabilitation assessing disease-related knowledge, health literacy, adherence to the Mediterranean Diet and self-efficacy. Physical activity was measured by number of steps per day using wearable activity tracking devices. Satisfaction with the educational materials was also evaluated by a survey with a 10 point Likert-type scale and yes/no and open-ended questions. Results: Eighty-one(99%) participants completed both assessments. There was significant improvement in disease-related knowledge(p < 0.001), physical activity(p < 0.001), and adherence to the diet(p = 0.005) post-rehabilitation. The number of participants that were classified as having "high health literacy skills" increased by 17%. Post-rehabilitation knowledge was associated with education level (ß = 0.430; p = 0.001),pre-rehabilitation knowledge (ß = 0.510; p = 0.002), and high health literacy skills (ß = 0.489; p = 0.01). Educational materials were highly satisfactory to participants. Conclusion: Significant increases in disease-related knowledge and health behaviors in patients attending hybrid models of cardiac rehabilitation are encouraging results that support the value of implementing comprehensive educational initiatives to programs in Spain. Innovation: This work presents preliminary evidence of the effectiveness of the first comprehensive education intervention that is open access and culturally adapted to people living with cardiovascular disease in Spain.